2017
DOI: 10.1016/j.rser.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Keep it local and fish-friendly: Social acceptance of hydropower projects in Switzerland

Abstract: Hydropower is the largest source of renewable electricity in the world, but despite being a mature and clean energy technology it has also been the subject of ecological and social conflict. Literature suggests that the social acceptance of renewable energy can be increased by respecting procedural justice (fair, participatory planning processes) and distributional justice (fairly allocating costs and benefits). However, empirical evidence about how justice considerations are related to the expansion of hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 53 publications
9
64
0
7
Order By: Relevance
“…Previous studies have shown that disclosing the country of origin can have an affective meaning to people, due to the emotional connotations people have with a specific country or due to the normative meaning when people view purchasing local goods as a way to support the local economy [39,64]. The identification of preferences of Swiss consumers for locally produced PV panels from Switzerland over German PV panels is in line with previous findings from the renewable energy literature that also reveals Swiss citizens' strong preference for Swiss over German ownership of hydropower plants [65]. This strong preference should encourage manufacturers from Switzerland to emphasize the Swiss origin of the panels in their marketing efforts to differentiate themselves on the basis of the country-of-origin effect.…”
Section: Conclusion and Policy And Marketing Implicationssupporting
confidence: 84%
“…Previous studies have shown that disclosing the country of origin can have an affective meaning to people, due to the emotional connotations people have with a specific country or due to the normative meaning when people view purchasing local goods as a way to support the local economy [39,64]. The identification of preferences of Swiss consumers for locally produced PV panels from Switzerland over German PV panels is in line with previous findings from the renewable energy literature that also reveals Swiss citizens' strong preference for Swiss over German ownership of hydropower plants [65]. This strong preference should encourage manufacturers from Switzerland to emphasize the Swiss origin of the panels in their marketing efforts to differentiate themselves on the basis of the country-of-origin effect.…”
Section: Conclusion and Policy And Marketing Implicationssupporting
confidence: 84%
“…Other variables affecting investment willingness encompass educational level, house ownership, as well as preference for maintaining comfort, status quo, and social class. Of these, high educational Sustainability 2019, 11, 5012 5 of 18 level [29,34] and house ownership [23] have been found to have a positive effect on an individual's willingness to invest in renewable energy, while higher educational levels are also linked to increased concerns about the ecological impacts of renewable installations [40]. Meanwhile, in their decision to change their current fossil fuel-based energy system, homeowners can be affected by social norms [9] and their wish to maintain their accustomed comfort and current status quo [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite being the most widely applied renewable source to date, it is typically a CGRS with heavy landscape impacts, especially ecosystem damage (Tabi & Wüstenhagen, 2017). Increasingly, small and micro-hydro units are providing a DGRS alternative with reduced ecological impact, under the condition of careful siting that takes ecological and landscape concerns into account (Armstrong & Bulkeley, 2014).…”
Section: Dg Infrastructure and Landscape Issuesmentioning
confidence: 99%